2006
DOI: 10.4049/jimmunol.177.2.804
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Alterations in EphA4-Deficient Mice

Abstract: In the present work, we have demonstrated in vivo an altered maturation of the thymic epithelium that results in defective T cell development which increases with age, in the thymus of Eph A4-deficient mice. The deficient thymi are hypocellular and show decreased proportions of double-positive (CD4+CD8+) cells which reach minimal numbers in 4-wk-old thymi. The EphA4 −/− phenotype correlates with an early block of T cell precursor differentiation that results in accumulation of CD44−CD25+ triple-negative cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 71 publications
(76 reference statements)
9
67
1
Order By: Relevance
“…Moreover, the expression of the different members of the family seems to be regulated, and several Ephs and ephrins appear on the same thymic cell type and at the same thymocyte developmental stage [17,18], indicating a wide plasticity that allows different combinations of signals. We have previously demonstrated a general role for the EphA subfamily in thymocyte development [16] and a more specific role for EphA4 in the thymic epithelial network organization which indirectly affected the T cell development [19]. Recent evidence of regulation of anti-CD3 antibody-induced apoptosis has also been reported [20].…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, the expression of the different members of the family seems to be regulated, and several Ephs and ephrins appear on the same thymic cell type and at the same thymocyte developmental stage [17,18], indicating a wide plasticity that allows different combinations of signals. We have previously demonstrated a general role for the EphA subfamily in thymocyte development [16] and a more specific role for EphA4 in the thymic epithelial network organization which indirectly affected the T cell development [19]. Recent evidence of regulation of anti-CD3 antibody-induced apoptosis has also been reported [20].…”
Section: Introductionmentioning
confidence: 89%
“…81 In addition, it has been shown that some chemorepellent molecules, including semaphorins and ephrins, affect thymocyte differentiation during their development. [82][83][84] Sema3E, which interacts with plexin-D1 in an NP-1-independent manner, was recently reported to participate in thymocyte development. 82 Plexin-D1 expression is high in CD4 1 CD8 1 thymocytes (double-positive, DP) but decreased in single-positive cells.…”
Section: Semaphorins In the Thymusmentioning
confidence: 99%
“…The defects seen in thymocyte maturation in Eph-or ephrin-deficient thymi are thought to result from abnormal development of the stromal cell compartments (27) and modulation of T cell responses (28). For example, EphB2-and/or EphB3-deficient mice exhibit decreased numbers of thymocyte subsets (29), the lack of EphA4 expression results in hypoplastic thymi and decreased numbers of double-positive (CD4 + CD8 + ) thymocytes (27), and blocking fetal thymic organ cultures with EphB2/Fc or ephrin-B1/Fc fusion proteins decreases doublepositive and single-positive T cell populations (30).…”
mentioning
confidence: 99%